If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + -1) + y(x + -1) = 0 Reorder the terms: x(-1 + x) + y(x + -1) = 0 (-1 * x + x * x) + y(x + -1) = 0 (-1x + x2) + y(x + -1) = 0 Reorder the terms: -1x + x2 + y(-1 + x) = 0 -1x + x2 + (-1 * y + x * y) = 0 Reorder the terms: -1x + x2 + (xy + -1y) = 0 -1x + x2 + (xy + -1y) = 0 Reorder the terms: -1x + xy + x2 + -1y = 0 Solving -1x + xy + x2 + -1y = 0 Solving for variable 'x'. The solution to this equation could not be determined.
| -5(t-5)-(t+3)=2 | | .035x50 | | -1/3*-5 | | y^4+3y^3+y^2=0 | | x-9=-6+3 | | 116=4x+2y | | 9-6t+4t^2=0 | | 4(3c-1)-6=7c+5 | | 3×2x=10+x | | 2x+6+3x+99=180 | | 4(3)2+2(2)-5= | | (4x-25) | | (x-1)(x-8)= | | 4=v/11-2 | | x-5y=-1 | | 6(s+1)=4(s+2) | | 3x^2y-2xy^2=0 | | q/5=-7.35 | | 5x+10=12x-4 | | 3(2r+8)=6(3r-24) | | 5(2r+2)=4(3r-1) | | 8-3x=4x+22 | | 5x+3andTQ=48 | | 259x+264/462 | | 9y-9=7y-5 | | 4t+5=5 | | 3h+10=5h+4 | | x^2-6x+=0 | | 5h=3h+18 | | y-3y=12 | | 72a-96b-48c= | | 7(x-3)+2x=24 |